Atomic-Level Structural Dynamics of Polyoxoniobates during DMMP Decomposition - Qi Wang (Nature Portfolio, 2017)
Abstract Ambient pressure in situ synchrotron-based spectroscopic techniques have been correlated to illuminate atomic-level details of bond breaking and formation during the hydrolysis of a chemical warfare nerve agent simulant over a polyoxometalate catalyst. Specifically, a Cs8[Nb6O19] polyoxoniobate catalyst has been shown to react readily with dimethyl methylphosphonate (DMMP). The atomic-level transformations of all reactant moieties, the [Nb6O19]8− polyanion, its Cs+ counterions, and the DMMP substrate, were tracked under ambient conditions by a combination of X-ray absorption fine structure spectroscopy, Raman spectroscopy, and X-ray diffraction. Results reveal that the reaction mechanism follows general base (in contrast to specific base) hydrolysis. Together with computational results, the work demonstrates that the ultimate fate of DMMP hydrolysis at the Cs8[Nb6O19] catalyst is strong binding of the (methyl) methylphosphonic acid ((M)MPA) product to the polyanions, which ultimately inhibits catalytic turnover.